2016
DOI: 10.1097/ta.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications of angioembolization for hepatic trauma

Abstract: Background The liver is one of the most frequently injured abdominal organs. Hepatic hemorrhage is a complex and challenging complication following hepatic trauma. Significant shifts in the treatment of hepatic hemorrhage, including the increasing use of angioembolization, are believed to have improved patient outcomes. We aimed to describe the efficacy of angioembolization in the setting of acute hepatic arterial hemorrhage, as well as the complications associated with this treatment modality. Methods A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 53 publications
8
83
0
4
Order By: Relevance
“…With regard to efficacy in this study, the rate of effective haemorrhage control without repeated TAE or additional surgical intervention was 93% for all paediatric patients, which was similar to that for adult patients (88%). The success rate of TAE was also similar to the results of previous studies that reported 75-100% as the success rate of TAE in paediatric cohorts [8,20,21] and 77-100% in cohorts with both paediatric and adult patients [5,6]. Although we cannot compare the mortality rate directly between the paediatric and adult patients because there are differences in the injury site and severity between two groups, we found that the SMR of paediatric patients was lower than that of adults in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With regard to efficacy in this study, the rate of effective haemorrhage control without repeated TAE or additional surgical intervention was 93% for all paediatric patients, which was similar to that for adult patients (88%). The success rate of TAE was also similar to the results of previous studies that reported 75-100% as the success rate of TAE in paediatric cohorts [8,20,21] and 77-100% in cohorts with both paediatric and adult patients [5,6]. Although we cannot compare the mortality rate directly between the paediatric and adult patients because there are differences in the injury site and severity between two groups, we found that the SMR of paediatric patients was lower than that of adults in this study.…”
Section: Discussionsupporting
confidence: 90%
“…There were no complications in paediatric patients, when we used the same diagnostic and therapeutic algorithm for blunt torso trauma patients with haemorrhage for all ages at our centre, which the complication rate in this study is similar to that reported in previous studies as mentioned 0-7% [4][5][6][7][8]. With regard to additional urgent therapy before and after the TAE, there were no significant differences in the proportion of patients who underwent urgent blood transfusion, resuscitative endovascular balloon occlusion of the aorta (REBOA), or surgical intervention in this study between paediatric and adult patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The largest systematic review for hepatic AE by Green et al found 15% developed hepatic necrosis across the series with a range of 0e43%. 9 Dabbs et al in contrast reported a significantly higher rate of hepatic necrosis, with 42% developing necrosis in seventy-one patients who underwent hepatic AE. We 27,28 The lower rate of hepatic necrosis likely represents improvements in catheter technology with the development of microcatheters allowing for improved arterial selectivity.…”
Section: Discussionmentioning
confidence: 94%
“…11e13 These studies reported efficacy for hepatic AE ranging from 81 to 100%, while the systematic review by Green et al reported a 77e100% success rate. 9 However, hepatic AE has been associated with a high rate of complications including hepatic necrosis, gallbladder infarction, bile leaks, and perihepatic abscesses. The most recent report by Kong et al reported a 27% liver related complication rate in hepatic AE-treated patients since 2009.…”
Section: Introductionmentioning
confidence: 99%